Deaths in custody in Australia: National Deaths in Custody Program 2011–12 and 2012–13 - Ashleigh Baker
Abstract: The data presented in this report include frequencies of deaths in prison and police custody and information regarding the deceased, including demographic information and cause of death. Long term trends are also presented. In 2011–12 and 2012–13, there were 144 deaths in custody, 73 in 2011–12 (42 prison custody; 31 police custody and custody-related operations) and 71 in 2012–13 (53 prison custody; 18 police custody and custody-related operations). At June 30 2013 the total prison population in Australia was 30,775 (including 8,430 Indigenous prisoners; 27%). More than two-thirds of deaths in prison were due to natural causes (n=64), most commonly cancer. Hanging deaths accounted for 19 percent (n=17) of prison custody deaths. The number of police custody deaths in 2012–13 dropped significantly from 2011–12 and is the lowest recorded since the definition of police custody deaths was expanded in 1990